Entrepreneurship in Algeria:is it agoel or a means¨ Socio-analyticreading - Wahida, Wahida; Kechicheb, Moured (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
The emergence of entrepreneurship in Algeria was slow due to the ideological orientation of the state. It witnessed profound transformations starting from marginalization to legitimacy and then independence after adopting the market economy system, which imposed on the Algerian state to place entrepreneurship as a strategy in the various plans it carried out and its formulation of a set of laws, especially the investment law starting in 1993, in addition to the various support structures that work to finance small and medium enterprises and start-ups, which helped in the spread of a large number of them, as they witnessed a significant increase in recent years. This research paper aims to highlight the various circumstances in which entrepreneurship arose in Algeria and to know the various factors that helped in the emergence of small and medium enterprises and start-ups and how they developed, in addition to knowing the importance of the economic, political and social context for the dynamics of entrepreneurship. In this research paper, we relied on the historical approach based on monitoring historical events, which helped us follow the history of the phenomenon of entrepreneurship in Algeria and its development over different historical periods, in addition to the descriptive approach that helped us describe and analyze the phenomenon in each of the historical periods it went through. We have concluded that the Algerian government has realized the importance of entrepreneurship in achieving economic growth, which has contributed to its emergence in its various policies. However, it has not provided the appropriate economic climate that facilitates the pace of its development. Moreover, the economic, social and even political context has greatly affected the rapid development of entrepreneurship in Algeria.